High-performance all-polymer solar cells based on fluorinated naphthalene diimide acceptor polymers with fine-tuned crystallinity and enhanced dielectric constants. (March 2018) - Xu, Xiaofeng; Li, Zhaojun; Wang, Junke; Lin, Baojun; Ma, Wei; Xia, Yangjun; Andersson, Mats R.; Janssen, René A.J.; Wang, Ergang
Abstract: Growing interests have been devoted to the synthesis of polymer acceptors as alternatives to fullerene derivatives to realize high-performance and stable all-polymer solar cells (all-PSCs). So far, one of the key factors that limit the performance of all-PSCs is low photocurrent density (normally < 14 mA/cm 2 ). One potential solution is to improve the dielectric constants ( ε r ) of polymer :polymer blends, which tend to reduce the binding energy of excitons, thus boosting the exciton dissociation efficiencies. Nevertheless, the correlation between ε r and photovoltaic performance has been rarely investigated for all-PSCs. In this work, five fluorinated naphthalene diimide (NDI)-based acceptor polymers, with different content of fluorine were synthesized. The incorporation of fluorine increased the ε r of the acceptor polymers and blend films, which improved the charge generation and overall photocurrent of the all-PSCs. As a result, the PTB7-Th:PNDI-FT10 all-PSC attained a high power conversion efficiency (PCE) of 7.3% with a photocurrent density of 14.7 mA/cm 2, which surpassed the values reported for the all-PSC based on the non-fluorinated acceptor PNDI-T10. Interestingly, similarly high photovoltaic performance was maintained regardless of a large variation of donor:acceptor ratios, which revealed the good morphological tolerance and the potential for robust production capability of all-PSCs. Graphical abstract: fx1 Highlights: Polymer structure design to improve dielectric constants of acceptor polymers. The first study on how dielectric constants affect the performance of all-polymer solar cells. The first report on high-performance all-polymer solar cells with extreme D:A ratios.